AT_CHLORO: A Chloroplast Protein Database Dedicated to Sub-Plastidial Localization - Bruley, Christophe; Dupierris, Véronique; Salvi, Daniel; Rolland, Norbert; Ferro, Myriam (Frontiers in Plant Science, 2012)
AT_CHLORO (www.grenoble.prabi.fr/at_chloro/) is a database dedicated to sub-plastidial localization of A. thaliana chloroplast proteins. This information was infered from proteomics experiments obtained from a comprehensive study that allowed the identification of proteins from envelope, stroma and thylakoid sub-compartments (Ferro et al., 2010). In addition to current knowledge regarding sub-plastidial localization, AT_CHLORO provides experimental data that allowed curated information regarding sub-cellular localizations of chloroplast proteins to be given. A specific focus was given to proteins that were identified in envelope fractions and for which expert functional annotation was provided. The present mini review shows the specificities of AT_CHLORO with respect to available information, data export options and recent improvements in data representation.